Heuristic Design of Cathode Hybrid Coating for Power‐Limited Sulfide‐Based All‐Solid‐State Lithium Batteries - Liang, Yuhao; Liu, Hong; Wang, Guoxu; Wang, Chao; Li, Dabing; Ni, Yu; Fan, Li‐Zhen (Advanced energy materials, 2022)
Engineered cathode active materials are critical for the cycling stability and power capability of sulfide‐based all‐solid‐state lithium batteries (ASSBs), yet it is challenging to construct uniform coverage via a scalable approach. In addition, the implication of dielectric coatings for electronic migration blocking in the composite cathode is neglected habitually. A heuristic “polymer‐patched inorganic” cathode coating strategy is presented herein. Single‐crystalline LiNi0.6Co0.2Mn0.2O2 (SNCM) particles are uniformly coated with a hybrid layer comprising nanoscale Li1.4Al0.4Ti1.6(PO4)3 (LATP) and cyclized polyacrylonitrile (cPAN), via a scalable solution‐based method. The LATP coating ensures rapid Li+ transfer across the interface and offers high oxidation tolerance. cPAN partially‐submerges and patches the imperfections of the LATP coating layer, producing a high‐quality protective coating without compromising electronic transfer. Accordingly, sulfide‐based ASSBs employing the hybrid‐modified SNCM cathode demonstrate competitive electrochemical performance in terms of capacity retention (72.7% over 500 cycles, at 0.5 C), and rate capability (87.3 mAh g−1 at 2 C, 5 times that of the pristine SNCM). Significant improvements are attributed to the homogeneity and functionality of the coating, which mitigates parasitic reactions at the interface while simultaneously preserving indispensable electronic percolation. This work offers a brand‐new cathode coating protocol for sulfide‐based all‐solid‐state to achieve longevity and good power. A heuristic “polymer‐patched inorganic” cathode coating strategy applied in sulfide‐based all‐solid‐state batteries is proposed to mitigate interfacial parasitic reactions while simultaneously assuring indispensable electronic percolation. The novel hybrid coating can be prepared by a scalable and convenient solution‐based method, and allows all‐solid‐state lithium batteries to achieve longevity and good power.